HOW WORKING FROM HOME SHAPES PUBLIC SECTOR EFFICIENCY THROUGH DIGITAL COMPETENCY IN MALAYSIA - HASBULLAH OTHMAN; IRWAN IBRAHIM (Quantum Journal of Social Sciences and Humanities, 2026)
The implementation of Work From Home (WFH) arrangements within the Malaysian public sector has transformed operational coordination, administrative communication, and supply chain related activities among government agencies. This study examines the effect of Work From Home practices on operational efficiency and supply chain coordination among public servants in Negeri Sembilan, Malaysia. The study further investigates the mediating role of digital competency in strengthening operational performance under remote working conditions. A quantitative cross sectional survey design was employed involving 400 public servants from selected government agencies in Negeri Sembilan. Data were analysed using Statistical Package for the Social Sciences (SPSS) version 29 through descriptive analysis, Pearson correlation, multiple regression, and mediation analysis. The findings revealed that Work From Home practices significantly influence operational efficiency and supply chain coordination. Digital competency also emerged as a significant predictor and partial mediator between Work From Home practices and operational performance. The study contributes to operations management and public sector administration literature by demonstrating that digital readiness and organizational adaptability are essential in sustaining operational continuity under flexible work arrangements. The findings further provide practical and policy implications for future Work From Home implementation within Malaysian public sector organizations.